Gall stones: a fundamental clinical review - Iqbal, Muhammad Nouman; Iqbal, Muhammad Arslan; Javaid, Rukhsar; Abbas, Muhammad Waseem (International Journal of Research in Medical Sciences, 2019)
Formation of stones in the gall bladder is known as cholelithiasis. About 10% to 20% of Western population are suffering from gall stones and this percentage is increasing day by day. Biochemically gall stones are classified into black pigment stones, brown pigment stones and cholesterol stones. Gall stones can be anatomically located at two possible sites; in the gall bladder known as cholelithiasis and in the common bile duct known as choledocholithiasis. Gall stones may present with symptoms known as symptomatic gallstones or without symptoms known as asymptomatic gallstones. The major causes of gallstones are high cholesterol diet, low bile salt levels, decreased gall bladder motility etc. Obesity, female gender, family history, rapid weight loss and vitamin B12 or folic acid deficiency are considered as important risk factors in the development of gall stones. The clinical presentations include acute cholecystitis and febrile illness with pain and tenderness in the right upper quadrant (Murphy sign). Generalized body weakness and weight loss are considered as generalized symptoms of gallstones. The complications include cholangitis, empyema of gall bladder, pancreatitis, abscess formation, porcelain gall bladder and gall bladder perforation. The differential diagnosis of gall stones is carried out based on endoscopy, ALT and AST serum levels. Non-surgical treatment for gall stones is oral dissolution therapy. The standard surgical treatment for gall stones is cholecystectomy.